2020
DOI: 10.31341/jios.44.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Factors Influencing on Agile Practices for Software Development

Abstract: Agile practices are activities or actions that are utilized during software development to improve the quality and productivity of the resulting software. Those practices are influenced by a set of factors that affect the realization of their objectives. The purpose of this study is to determine the influence of organizational factors and the personnel working on the software development project to the agile practices. To this end, a model has been proposed that is composed of six critical success fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Based on our findings we identified that the practices in some studies are on a more detailed level (e.g. according to Arcos-Medina [6]). The list of agile practices without any redundancies is the basis for the following steps.…”
Section: Synthesizing Agile Practicesmentioning
confidence: 91%
See 1 more Smart Citation
“…Based on our findings we identified that the practices in some studies are on a more detailed level (e.g. according to Arcos-Medina [6]). The list of agile practices without any redundancies is the basis for the following steps.…”
Section: Synthesizing Agile Practicesmentioning
confidence: 91%
“…In total, the 37 studies list 944 agile practices. The count of listed agile practices in the included studies range from 4 [41] to 93 agile practices [6]. Almost half of the studies (17) list between 20 and 40 agile practices (see Figure 4).…”
Section: The Current State Of Agile Practicesmentioning
confidence: 99%
“…Many firms nowadays aspire to develop systems in a short amount of time and at a low cost [11]. They utilize agile approaches as a result they enable flexibility, allow modifications at any time, and are contributed to greater software quality [12] [11]. Despite the use of innovative approaches, a large number of IT initiatives fail.…”
Section: Assessment Of Rq1 What Are the Combinations Of Agile Methods...mentioning
confidence: 99%
“…Papers I have examined have a diverse perspective on software's quality. Many researchers define quality as satisfying the demands and expectations of customers, whereas [12] defines the 3 forms of the software quality: design quality, performance quality and adoption quality. Quality attributes can be broken down by these characteristics.…”
Section: Assessment Of Rq1 What Are the Combinations Of Agile Methods...mentioning
confidence: 99%
See 1 more Smart Citation